Studi Kepustakaan tentang Penerapan Konseling Cognitive Information Processing dalam Lingkup Pendidikan - Fijar Suwarno Putri; Wagimin Wagimin; Ulya Makhmudah (Jurnal Psikoedukasi dan Konseling)
Abstract: This study aims to describe the application of cognitive information processing (CIP) counselling in education. This research is qualitative research with a literature study design. The data sources used in this research are 20 library articles relevant to the research topic in the form of 14 international and six national scientific articles. Documentation is used to collect data. The data analysis technique in this study used qualitative techniques with content analysis. The results of this study include a description of the procedures, methods, objectives, suggestions, and success. The CIP counselling procedure has several meeting sessions, and the duration of time is adjusted to career problems. The stages used are the CASVE cycle (Communication, Analysis, Synthesis, Valuing, and Execution) and the seven-step service delivery sequence. CIP counselling method is group counselling. The target application of counselling from high school to college. Suggestions related to the application of counselling to improve the provision of counselling services in schools. The success of CIP counselling can solve various career problems for students.